Health beliefs and health seeking behaviors of army soldiers with tuberculosis - Tayawa-Villalba, Miriam
TUBERCULOSIS (TB) is a problem of global importance and considered the world's leading infectious killer. Eight million people develop the active disease and two million people die from this disease annually. In the Philippines, TB remains a major public health and socio-economic problem. It persists as one of the leading infectious but preventable diseases that have serious and debilitating effects on individuals, families and communities. It entails looking into the socio-economic, behavioral and cultural factors that affect the problem. It likewise requires understanding of the dynamics of the many facts of the problem at the individual, community and structural levels.